Study of a single-valve reciprocating expander. Issue 3 (August 2016) - Zhang, Xinjing; Xu, Yujie; Xu, Jian; Xue, Haobai; Chen, Haisheng
Abstract: The reciprocating expander is a small scale power generation device which could be extensively utilized in small scale compressed air energy storage (CAES) system, distributed renewable energy utilization, uninterruptible power supply, vehicle engine etc. In this paper, a simulation work of a single-valve reciprocating expander is carried out. The working performance, flow loss mechanism and its internal flow structure are studied in details. The flow losses are analyzed. It reveals that the flow speed is very high due to the large pressure difference during the air intake period. It also causes strong vortex flow inside the cylinder leading to a big loss of the total pressure. This study provides a fundamental understanding of the single-valve reciprocating expander and a reference for further optimization design. Highlights: A single-valve reciprocating expander is introduced with less parts, better inlet valve sealing performance and relatively higher efficiency. The expander's flow field and its characteristics are analyzed, and the flow loss mechanism is explained. The study reveals that the pressure loss is mainly caused by the air intake process because of the large pressure difference.